The effect of shame on depressive symptoms in people with and without chronic physical disease: Exploring the mediator role of self-compassion and committed action - Veiga, Daniela (2019)
Aim: The current study aimed at examining the potential mediator role of self-compassion and committed action on the link between shame and depressive symptomatology in people with and without a diagnosis of chronic disease. Additionally, differences between these two groups were explored regarding these variables. Method: The sample included 453 participants (223 with chronic disease and 230 without a diagnosis of chronic disease), who completed an online survey. Results: Participants with a diagnosis of chronic disease significantly (p < 0.05) presented higher levels of shame feelings and depressive symptoms, and lower levels of committed action than participants without a chronic disease. Nonetheless, no significant differences in self-compassion abilities were found between the groups. Correlational results revealed that shame was negatively associated with self-compassion and committed action, and positively with depressive symptomatology, in both groups. Path analysis results indicated that shame feelings have a significant impact on depressive symptomatology (explaining 41% of its variance), mediated through decreased self-compassion and committed action. A multi-group analysis revealed that this model was invariant between study groups. Conclusions: This study seems to provide important contributions to understand the protective impact of self-compassionate abilities and the adoption in committed action in mental health, both for people with or without a chronic disease diagnosis. Indeed, these processes appear to be important mediating mechanisms that seem to minimize the negative effects of shame on depressive symptomatology. These findings seem to support the development of more effective approaches for the promotion of psychological health for people with or without a chronic disease diagnosis.